232 DIFFERENTIAL GENETIC EXPRESSION AND REDUCED LONGITUDINAL FUNCTION IN PATIENTS WITH DIABETES AND SEVERE AORTIC STENSOIS WITH A NORMAL EJECTION FRACTION. (24th May 2013) - Ashrafi, R; Gerges, J Y; Hart, G; Boyett, M; Davis, G; Wilding, J
Abstract : Introduction: Aortic stenosis and type 2 diabetes mellitus are common conditions and patients with cardiovascular disease and type 2 diabetes tend to have a worse outlook than those with cardiovascular disease alone. We compared patients with severe aortic stenosis and diabetes to patients with severe aortic stenosis but no diabetes. We compared left ventricular (LV) function and expression of key genes in the left ventricle. Methods: Two groups of patients with severe aortic stenosis (AVA of 1.0 cm 2 or less and LV ejection fraction >55%) and with (n=6) or without (n=8) type 2 diabetes were referred for aortic valve replacement. Patients had a full echocardiogram with speckle tracking prior to their operation and had a single apical LV needle biopsy taken just prior to the initiation of cardio-pulmonary bypass. The biopsies were flash frozen for mRNA expression. Expression of 48 mRNAs (responsible for ion channels and involved in energy metabolism and contractile performance in the heart) was measured by qPCR. Expression was normalised to 18S and differences were assessed using Student's t-test (* P <0.05). Results: Mean patient characteristics (with standard deviations) in both groups are shown below: Mean echocardiogram parameters (with standard deviations) for the two groups are shown below: Of the 48 genetic targets tested on the tissue samples we found an increase in patients with diabetes: NFKB-a proinflammatory transcription factor KIR 2.1 and KIR 3.1- potassium channels NCX 1-sodium-calcium exchanger ANKRD1- a transcription factor We found a decrease in patients with diabetes in: HERG- a potassium channel MTATP 6- a mitochondrial energy production gene NAV 1.5- a sodium channel Discussion: We have shown a significant reduction in longitudinal left ventricular function (as evidenced by reduced MAPSE and longitudinal strain) in patients with diabetes mellitus and severe aortic stenosis compared to non diabetic controls. There was no difference in weight, BMI, waist circumference, normal ejection fraction, LV septal thickness and LV end diastolic volume. The left ventricular changes are accompanied by differential expression in several cardiac genes in patients with diabetes and may represent a subclinical cardiomyopathy that could be targeted for primary prevention of symptomatic cardiac disease.